Looking for sufficient change: Evaluation of counsellor training for STI syndromic management in India. (October 2016) - Vaz, Melita; Kadyan, Nisha; Chalil, Sumitha; Prasad, Turlapati L.N.; Singh, Aman Kumar
Highlights: Training counsellors for patient education related to syndromic management of STI has not been discussed in the literature before. National programme managers in India developed a competency-based approach to train a newly-constituted workforce. Conventional training had not demonstrated good results. Using this approach, they were able to improve the training process for counsellors and demonstrate improved change. Abstract: In India, public health care of Sexually Transmitted Infections is delivered through Designated STI/RTI Clinics (DSRCs) using syndromic management. This paper describes efforts, over three years, to improve in-service training for counsellors positioned at DSRCs—using a data approach. The programme managers realised, through rigorous monitoring of initial induction training reports that, while knowledge and attitudes of most trainees had improved as evident from t -tests, at least one-quarter scored worse on post-training assessments (n = 859). Therefore, they undertook a survey using a competency approach to diagnose what critical competencies are influenced through training: counselling skills, risk reduction suggestions, labelling male and female anatomy, record-keeping and STI patient education (n = 132). Survey results demonstrated that trainees failed to pass a two-thirds cutoff score in most competencies. These findings led the programme managers to modify training and implement tighter quality measures. In the second round of training – refresher training – outcomes on competency assessments before and after training showed more acceptable performance (n = 833). The paper describes how programme managers, after an acceptance of such initial short-comings, developed customized assessments when literature provided limited guidance and how they worked to achieve change that was acceptable for programme needs.